Istisna' (Manufacturing contract) In Islamic Banking and Finance: Law and Practice - Al-Amine, Muhammad Al-Bashir Muhammad (ASN, 2006)
The present book is an extensive and critical analysis of this contract from the classical sources of Islamic law and the practice of contemporary Islamic financial institutions . It addresses the nature of this contract, its conditions, the general and specific argument for the legality of this contract, its binding character and the seller's stipulation to preclude his liability from any defect in the manufactured commodity.